'A Final Solution for Humanity'? Modern Design and the Ambivalence of Redemption in Post-War West Germany. Issue 1 (April 2023) - Scholz, Natalie
Abstract : During the Third Reich, a modern shape of everyday objects was propagated as realising a German nation defined as an organic and racial entity. What happened to this cultural nexus after 1945? Historical scholarship has emphasized above all that modern design went on to be successfully framed as a cultural good that redeemed West Germany from the Nazi past. This redeeming opposition between the political meanings of modern design before and after 1945, however, appears less clear-cut if one acknowledges the structure of denial in post-war discourses by focussing on the silences, omissions and discrepancies in various publications. Such an analysis exposes how the coding of modern design as 'timeless' together with its promotion in the context of the Marshall Plan made it possible to blur any historical understanding of how the underlying notions of everyday aesthetics had been intertwined with racially loaded ideas of the German people. This obscurity in the context of a not yet decolonized West facilitated the continuing influence of at least some aspects of modern design's more troubling political legacies.